L'actualisation des noms sous-spécifiés dans le processus d'écriture enregistré en temps réel : considérations fonctionnelles - Georgeta Cislaru (Corela)
Semantically under-specified names (NSS) are functionally very skillful, and ensure connection or textual indexing functions. In this paper, we will focus on the production of NSSs during the writing process recorded in real time, in order to observe the discursive functioning of this nominal subcategory and the way it can help to structure discursive dynamics. We defend the idea that the strategies for the NSS production and use during the writing process offer an unprecedented insight into their textual functioning, and also make it possible to question the notion of sub-specification, apprehended in the dynamics of online updating and, as a result, put in relation with the notion of informational completion.